The Influence of Blood Contamination on Cerebrospinal Fluid Diagnostics - Schwenkenbecher, Philipp; Janssen, Theda; Wurster, Ulrich; Konen, Felix Franz; Neyazi, Alexandra; Ahlbrecht, Jonas; Puppe, Wolfram; Bönig, Lena; Sühs, Kurt-Wolfram; Stangel, Martin; Ganzenmueller, Tina; Skripuletz, Thomas (Frontiers in Neurology, 2019)
Background: Blood contamination due to traumatic lumbar puncture presents a diagnostic pitfall in cerebrospinal fluid (CSF) analysis. It is controversially discussed if phagocytosis of erythrocytes which can be found in the CSF after subarachnoid hemorrhage can also develop in vitro in the presence of artificial blood contamination. Furthermore, there is no consensus about the acceptable amount of artificial blood contamination on CSF protein results. Methods: Two measurement series were performed in order to investigate the role of artificial blood contamination on the possible development of erythrophages and siderophages in the CSF: 1) blood contamination was simulated in vitro by adding blood into the CSF. 2) CSF was investigated when blood contamination occurred during a traumatic lumbar puncture. In both types of experiments, CSF including blood was incubated for 24 hours and for 72h at room temperature or at 4°C. In the third measurement series, the effects of artificial blood contamination on CSF protein results were investigated. Blood contamination was simulated in vitro by adding different amounts of blood ending up with five different samples containing erythrocyte counts of 2500, 5000, 7500, 10000 and 20000 per µl CSF. Results: Cytological examination revealed no evidence of erythrophages or siderophages in vitro. In contrast, already a low blood contamination (2500 erythrocytes/µl CSF) led to false pathological results of total protein and albumin. Along with increasing amounts of blood, the frequency of false pathological protein results increased. A blood contamination of 5000 erythrocytes/µl CSF resulted in a false positive intrathecal IgM production in nearly every fifth patient. In contrast, blood contamination with 5000 erythrocytes/µl CSF was the acceptable amount of blood which did not lead to a false positive intrathecal synthesis of IgG and IgA. Conclusion: Erythrophages and siderophages do not develop in vitro. An extensive diagnostic work up for the source of blood in the CSF should be performed when erythrophages or siderophages are found in the CSF. The contamination of CSF with increasing volume of blood resulted in falsely elevated CSF protein concentrations. Hence, the amount of blood contamination has to be taken into consideration when interpreting CSF protein measurement results.